2002
DOI: 10.1093/jnci/94.3.205
|View full text |Cite|
|
Sign up to set email alerts
|

Dominant Negative ATM Mutations in Breast Cancer Families

Abstract: At least two ATM mutations are associated with a sufficiently high risk of breast cancer to be found in multiple-case breast cancer families. Full mutation analysis of the ATM gene in such families could help clarify the role of ATM in breast cancer susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
169
1
1

Year Published

2003
2003
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(183 citation statements)
references
References 36 publications
11
169
1
1
Order By: Relevance
“…In contrast, the family study conducted by ChenevixTrench et al (2002) found no IVS10-6T4G mutations in the 262 breast cancer patients who were unselected for family history; two were observed in the 76 multiple-case breast cancer families. Similar to our study's 7271T4G mutation prevalence of 0.08% (one out of 1149), Chenevix-Trench et al (2002) observed one mutation among 525 cases and 381 controls (0.11%); all women included in the study were under age 40. The prevalence of this mutation was greater among the high-risk families where one out of 76 (1.3%) carried the mutation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, the family study conducted by ChenevixTrench et al (2002) found no IVS10-6T4G mutations in the 262 breast cancer patients who were unselected for family history; two were observed in the 76 multiple-case breast cancer families. Similar to our study's 7271T4G mutation prevalence of 0.08% (one out of 1149), Chenevix-Trench et al (2002) observed one mutation among 525 cases and 381 controls (0.11%); all women included in the study were under age 40. The prevalence of this mutation was greater among the high-risk families where one out of 76 (1.3%) carried the mutation.…”
Section: Discussionsupporting
confidence: 88%
“…The incidence of breast cancer among heterozygous carriers in A-T families, along with the known biochemical interactions between the products of the ATM and BRCA1 genes, has suggested a role for ATM in breast cancer risk. The recent study by Chenevix-Trench et al (2002) reported a greatly elevated risk of breast cancer among five members from multiple-case breast cancer families, who were heterozygous for ATM gene mutations, 7271T4G or IVS10-6T4G. The estimated combined penetrance of the two mutations was 60% (32 -90%) to age 70 years.…”
mentioning
confidence: 99%
“…It has been postulated and supported by limited experimental evidence that the presence of ATM missense mutations, in contrast to ATM truncating mutations, may result in a different cellular phenotype after exposure to IR and alter the risk of developing cancers in heterozygote carriers (Stankovic et al, 1998;Gatti et al, 1999;Chenevix-Trench et al, 2002;Scott et al, 2002). We have investigated the constitutive levels of expression of the ATM gene and the in vitro cellular phenotype after exposure to IR in 14 heterozygote cell lines carrying different mutations located throughout the ATM gene, to assess whether mutation-type specific differences could be detected and whether such end points could provide a reliable assay for the identification of ATM carriers.…”
Section: Discussionmentioning
confidence: 99%
“…To resolve this paradox, it has been hypothesised that there are two populations of AT carriers, one group with a truncating allele coupled with a normal allele (AT hets trunc ) and a second group with a missense mutation coupled with a normal allele (AT hets mis ), and that the latter group might be more prone to cancer development (McConville et al, 1996;Gatti et al, 1999;Meyn, 1999). Indeed, there is some experimental evidence that carrying an ATM missense mutation could lead to a dominantnegative phenotype in human cell lines (Chenevix-Trench et al, 2002;Scott et al, 2002), with competition between the mutant and the wild-type forms of the ATM protein.…”
mentioning
confidence: 99%
“…Cell extracts were prepared by lysis in Universal immunoprecipitation buffer (50 mM Tris -HCl, pH 7.4, 150 mM NaCl, 2 mM EDTA, 25 mM NaF, 25 mM b-glycerophosphate, 0.1 mM sodium orthovanadate, 0.1 mM phenylmethylsulphonyl fluoride, 5 mg ml À1 leupeptin, 1 mg ml À1 aprotinin, 0.2% Triton X-100, 0.3% IGEPAL). In all, 50 mg of cell extract was separated by SDS -PAGE, transferred to nitrocellulose and membranes probed with any of the following: a-CHK2 Thr68-P (Cell Signalling, USA), a-CHK2 (N17, H300, Santa Cruz, USA), a-CDC25A F6 (Santa Cruz, USA), a-PP2A-Ab (C-20,Cell Signalling, USA), a-p53 D01 (Novacastra Laboratories, UK), a-p53 Ser15-P (Cell Signalling, USA), polyclonal a-ATM (residues 250 -522) (Chenevix-Trench et al, 2002).…”
Section: Protein Extracts and Western Blottingmentioning
confidence: 99%